Implementasi Algoritma Modular Multiplication Based Block Cipher dalam mengamankan Data Teks - Anita, Feri (LPPM UNIKA Santo Thomas Medan, 2018)
Securing text data is very necessary to secure a data so that it is not stolen by irresponsible parties. Cryptography is one technique that can be used to secure data, namely by encoding the original data that is understood to be incomprehensible data. Cryptography is one way that is used to secure a data. Cryptography has several algorithms, one of which is a modular mulitiplication based block cipher algorithm which is one of the classic cryptographic algorithms that uses substitution in encoding data. Modular multiplication based block ciphers use 128-bit keys and an iterative algorithm consisting of linear steps (such as XOR and key applications) and parallel applications of four non-linear substitutions that can be reversed.